Pelatihan Pembuatan Sabun Padat Rumahan Berbasis Turunan Minyak Sawit Kepada Remaja Masjid IKRIA - Zakwan, Zakwan; Rahimah, Rahimah; Purjianto, Purjianto; Raja, Pada Mulia; Giyanto, Giyanto; Junaidi, Junaidi; Widjajanto, Adi; Isra, Marzuti; Roosmawati, Febriana; Sinuhaji, Yose Andrea (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2025)
Soap is one of the cleaning materials whose use is evenly distributed in every mosque, house and other public facilities. The relatively simple process of making soap should be an opportunity for the community to individually make soap, so as to increase community income and produce environmentally friendly soap. This community service aims to train the Al-Ikhwan Islamic Youth Association (IKRIA) Martubung Village, Medan Labuhan Subdistrict, Medan City. Homemade soap production has promising business activity prospects for IKRIA Mosque Teenagers. Home-made soap products can be an alternative to commercial solid soap for bathing or washing. Furthermore, soap making can be developed into natural soaps that are healthy and environmentally friendly. The problem of the Mosque Youth is that there is no basic knowledge related to making solid soap based on palm oil derivatives, so it is necessary to conduct practical training in making solid soap on a home scale. The training methods carried out were lectures, discussions and continued with solid soap production practices. This training activity is expected to increase the enthusiasm and knowledge of the IKRIA Mosque Youth to try to produce solid soap at home, so that it can increase the income of the Mosque Youth individually and collectively.